IMPLEMENTASI ISBAT NIKAH MASSAL DALAM PERSPEKTIF KOMPILASI HUKUM ISLAM - Kurniawan, Achmad Alfan; Rahmadhani, Aulia (al-Rasῑkh: Jurnal Hukum Islam, 2024)
Marriage, as stipulated by laws and regulations, requires documentation by an authorized official. Nonetheless, numerous marriages remain unregistered, as observed in Lampihong District, Balangan Regency, South Kalimantan, resulting in some individuals lacking a marriage certificate to validate their union. In response to this issue, KUA officials initiated mass marriage isbat to facilitate the issuance of marriage certificates. This study aims to elucidate the mass marriage isbat in Lampihong District and its relevance to the Compilation of Islamic Law (KHI). Employing an empirical legal research methodology with a case study approach and data were collected through interviews, the findings indicate that mass marriage isbat has been conducted in Lampihong District from 2019 to 2023, involving a total of 218 participants. This initiative aligns with Articles 5, 6, and 7 of the KHI. While these articles do not explicitly outline the procedure, the implementation of mass marriage isbat is deemed permissible and valid, as there are no prohibitions against its collective execution. Participants of the mass marriage isbat reported various advantages, particularly concerning the legitimacy of population administration, the safeguarding of marital rights and responsibilities, and the fulfillment of children’s needs.